The Effect of a Six Week Program of Systematic Training on Counsellors - Conklin, R. C.; Altmann, H. A.; Boak, T. (Canadian Journal of Counselling and Psychotherapy, 2012)
A group of graduate students were trained according to a popular "helping" model which purports to increase the ability to be facilitative. It was found that graduates were more facilitative after training, were able to train others, and that this type of facilitation ability may be related to self-facilitation. Results should be interpreted in light of the fact that there was no control group and that the measures of facilitation were of a paper-pencil variety rather than simulations of actual interaction. Un groupe d'étudiants inscrits aux études supérieures ont reçu un entraînement selon un modèle populaire d'assistance qui réclame pouvoir augmenter l'habileté d'aider le client. On a observé qu'après leur entraînement, ces étudiants possédaient cette habileté à un degré plus avancé, étaient capables d'entrainer d'autres personnes, et que ce genre d'habileté pouvait s'apparenter à la facilitation de soi. L'interprétation des résultats doit tenir compte du fait qu'il n'y avait pas de groupe contrôle et que les mesures employées étaient du type "crayon-papier" plutôt que des simulations de véritables interactions.